Academic insights and industry experiences: FIN388 visit to MBSB Bank / Norazimah Mejri - Mejri, Norazimah (Corporate Communication Unit, UiTM Mukah Campus, 2024)
On June 14, 2024, students enrolled in the Ethics and Governance in Financial Services (FIN388) course participated in an academic visit to the Mukah branch of MBSB Bank. This visit was designed to provide students with practical exposure to workplace operations and enhance their understanding of the critical role that ethics and governance play in financial institutions.